Leishmaniasis: the healthcare professionals' knowledge in endemic area - Júlia Alves Menezes; Kamila Nunes Maia; Rafael Negreiros Verne; Ana Paula Madureira; Virgínia Torres Schall; Carina Margonari de Souza (Universidade de Fortaleza, 2014)
Objective: To assess the knowledge about leishmaniases among healthcare professionals of an endemic municipality of the state of Minas Gerais-Brazil. Methods: Cross-sectional study conducted with 228 professionals (95 zoonosis professionals, 83 community health agents, 18 doctors, 17 nurses, 8 dentists and 7 veterinarians) of the municipality of Divinópolis - Minas Gerais between July and November 2009. It was used a structured questionnaire, previously validated, containing objective questions about the disease. Analyses were performed using the Statistical Analysis System. Results: The professional category that obtained the best mean scoring answers was the veterinarians (8.3), followed by the doctors (8.1), while community health agents had the lowest mean scoring (6.7). The adequate answers with the lowest percentage of correct answers were: preventive measures (42.5%), clinical manifestations (25.9%), popular names (20.6%) and transmission (20.2%). Although zoonosis professionals and health community agents presented the highest percentage of wrong answers, they were the ones - along with veterinarians - who answered most of the questions about preventive measures right. Conclusion: Conceptual gaps were observed among the healthcare professionals participating in this research, reinforcing the need to implement continuing education processes for these professionals, contextualizing the information on leishmaniases according to the reality studied. doi:10.5020/18061230.2014.p207